Analysis of the Shear Capacity of Ultrahigh Performance Concrete Beams Based on the Modified Compression Field Theory - Wei Feng; Hongming Feng; Zhijun Zhou; Xiongwei Shi (Advances in Materials Science and Engineering)
An analysis model of the shear capacity of prestressed ultrahigh performance concrete (UHPC) beams under the combined action of bending and shearing was established in this paper based on the modified compression field theory and by considering the unique material constitutive relation of UHPC. Shear tests were performed using three prestressed UHPC-T beams with different shear-span ratios to verify the correctness of the model. The results showed that the shear-span ratio greatly influenced the shear capacity and failure modes of UHPC-T beams. Upon increasing the shear-span ratio, the failure modes of the three beams were inclined compression failure, shear compression failure, and diagonal tension failure, successively. When the shear-span ratio changed from 1.04 to 2.12, the shear bearing capacity decreased greatly; however, when the shear-span ratio changed from 2.12 to 3.19, the decrease of the shear bearing capacity was very small. In addition, the MCFT analysis model was used to analyze the experimental data, and the predicted results were in good agreement, which proved the applicability of the model. Finally, according to the existing shear test results of UHPC beams and based on the main influencing factors, a simplified formula for predicting the shear capacity of UHPC beams was obtained by fitting. Comparing the MCFT model with the results of other pieces of literature, this formula accurately predicted the shear capacity of UHPC beams. The MCFT model and the simplified formula presented in this paper provide a powerful tool for predicting the shear performance of UHPC-T beams, which will contribute to the design and analysis of UHPC-T beams.